UPAYA MENINGKATKAN HASIL BELAJAR MEMBACA PERMULAAN MELALUI METODE KARTU SUKU KATA PADA SISWA KELAS I SDN 52 KOTA TERNATE - Marasabesy, Anwar; Wahid, Santi M.J. (EDUKASI, 2022)
The expected objectives of this study are to investigate the use the Reading method with Syllable flash Card in Indonesian language learning in the first years of State elementary school and to find out students’ learning outcomes after using the Reading method with Syllable Card. This research is a Classroom Action Research (CAR). This research includes Planning, Implementation, Observation/Observation, and Reflection which are sequential steps in each cycle. There are 28 students of elementary school participated in this research. Data were collected through test. Data were analyzed using descriptive analysis. The results of data analysis in the first cycle shows that the number of students who completed was 6 students with an average number of 21.42% and who did not complete were 22 students with an average number of 78.57%. Meanwhile, in the second cycle, 21 students were completed with an average score of 75% and those who did not complete were 7 students with an average score of 25%. Thus, the observations in the first cycle to the second cycle show that the target of completeness, it means that this research was no longer continued in the next cycle.